2011
DOI: 10.1002/jmv.22111
|View full text |Cite
|
Sign up to set email alerts
|

Analyses of human papillomavirus genotypes and viral loads in anogenital warts

Abstract: Condylomata acuminata (genital warts) are the most common sexually transmitted viral diseases. These lesions are caused by infection with mucosal human papillomaviruses (HPVs). However, there is limited information on HPV strain distribution involved in the molecular pathogenesis of these lesions. To address this, the strain prevalence and the frequency of multiple HPV infections were determined in wart tissue obtained from 31 patients attending a wart clinic. These lesions were bisected and subjected to paral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
54
1
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(63 citation statements)
references
References 32 publications
4
54
1
2
Order By: Relevance
“…Samples for HPV testing taken from gynecologists were sent at same conditions. Samples were analyzed by general primer GP5+/GP6+-based polymerase chain reaction (PCR) and genotyped by Luminexbased multiplexed genotyping (MPG) for detection of 19 HR HPV genotypes (HPV 16,18,31,33,35,39,45,51,52,56,58,59,68,26,53,66,70,73, and 82) and 7 low-risk (HPV 6, 11, 42, 43, 54, 57, and 72) HPV genotypes (multiplexed HPV genotyping, Multimetrix, Heidelberg, Germany).…”
Section: Sampling and Hpv Testingmentioning
confidence: 99%
“…Samples for HPV testing taken from gynecologists were sent at same conditions. Samples were analyzed by general primer GP5+/GP6+-based polymerase chain reaction (PCR) and genotyped by Luminexbased multiplexed genotyping (MPG) for detection of 19 HR HPV genotypes (HPV 16,18,31,33,35,39,45,51,52,56,58,59,68,26,53,66,70,73, and 82) and 7 low-risk (HPV 6, 11, 42, 43, 54, 57, and 72) HPV genotypes (multiplexed HPV genotyping, Multimetrix, Heidelberg, Germany).…”
Section: Sampling and Hpv Testingmentioning
confidence: 99%
“…3,4 A quadrivalent vaccine also protects against 2 low-risk types of the virus, which are responsible for 90% of genital warts (GW). 5,6 Although GW are not a life-threatening condition, they can have a significant negative impact on quality of life. 7 Furthermore, with the development and subsequent delivery of new vaccines, HPV-related cancers and infections can be greatly reduced in the future.…”
Section: Introductionmentioning
confidence: 99%
“…The synchronous infection of oncogenic and nononcogenic HPV has been supported by a HPV DNA analysis study on formalin-fixed paraffin-embedded cervical tissue blocks of 410 Thai women with LSIL+which showed that the most common triple HPV infection included HPV 11/16/18 (54.9%) (Suthipintawong et al, 2011), while another study in the United Kingdom using linear array assay on specimens of AGWs demonstrated that, of these, 35.5% also contained HPV 16 or 18 (Ball et al, 2011). Although no HPV DNA analysis was performed in the present study, a previous study using the polymerase chain reaction (PCR) in liquid-based cytology (LBC) of 1,662 Thai women showed that 30% of LSIL+contained oncogenic HPV types (Chansaenroj et al, 2010).…”
Section: Discussionmentioning
confidence: 96%
“…The annual incidence of AGWs is 160-289 per 100,000 and the overall prevalence ranges from 0.13-0.56% (Patel et al, 2013). Human papillomavirus (HPV) infection type 6 and 11, which are non-oncogenic types, account for more than 90% of the clinical manifestations as being confirmed by a deoxyribonucleic acid (DNA) analysis of wart specimens (Ball et al, 2011). The virus may persist at the affected sites for up to 12 months without any signs of inflammation (Mariani and Venuti, 2010) resulting in the long transmissible period.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation